Behavior and Factors Causing Plagiarism Among Undergraduate Students in Accomplishing the Coursework on Religion Education Subject - Engkizar, Engkizar; Alfurqan, Alfurqan; Murniyetti, Murniyetti; Muliati, Indah (Khalifa: Journal of Islamic Education, 2018)
The objectives of this study were to analyze the behavior and causal factors of plagiarism among the undergraduate students in accomplishing their coursework in Islamic religion subject. The study used methods combination of qualitative and quantitative research or Exploratory mixed methods designs. Qualitative data were taken from 15 papers of group works in the subjects of Islamic religion, while quantitative data were taken using questionnaires towards 80 students who are taking course in Islamic religion at State University of Padang (UNP). Data taken from papers of groupwork were analyzed thematically with method of data collection, data reduction, data presentation and taking conclusion, while questionnaires were analyzed descriptively using SPSS software version 18.0 for Windows.Results of the document analysis found that there are three forms of behavior of student plagiarism in accomplishing the coursework, first: by quoting the entire writings of the other person without mentioning the source, second: by quoting part / half of the text/writings of others, third: by quoting the writing of others then converted into their own statements. While there are eight factors that cause plagiarism which are: not understand about plagiarism, the student’s instant culture in accomplishing academic tasks, the high volume of academic tasks given by lecturers, students’ low interest in reading, not enough time to find the answer in the book, the ease of Information Technology, low purchasing power and lack of knowledge in how to write a scientific papers.